VALUATION OF SHARES BASED ON THE COST APPROACH - Botirkhoja Aziza Fakhmuddin kizi (Modern American Journals, 2025)
The article considers the valuation of shares based on the cost approach. The cost approach to valuing shares is based on the assertion that the cost of securities is comparable to the costs that must be incurred to create a similar company. The cost of shares in this case is equated to the market value of the replaced enterprise. The advantages and disadvantages of the cost approach are given. The main methods of the cost approach to business valuation are highlighted. Their strengths and weaknesses of the cost approach to business valuation are determined.
Keywords: Valuation, value, investments, methods, assets, shares, cost approach